Implikasi Aliran Filsafat Pendidikan dalam Pengembangan Kurikulum Pendidikan Islam - Ali Muttaqin (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2016)
Islamic education phenomenon with its kinds and shapes has good philosophic evidence. Philosophy of education is application of philosophyc ideas in education which has essential values to aim the purpose and the performance of Islamic education. Generally, the tendencies in philosophy had created the typology of Islamic education philosophy. Its tendencies influenced the development Islamic education curriculum. This paper tries to explain the tendency of education philosophy which influenced Islamic education curriculum.Keyword : Philosophy , Islamic education curriculum